CRE-Ter enhances murine bone differentiation, improves muscle cell atrophy, and increases irisin expression - Sompot Jantarawong; Wipapan Khimmaktong; Pharkphoom Panichayupakaranant; Yutthana Pengjam (PLoS ONE, 2025)
Ternary complex of curcuminoid-rich extract (CRE-Ter) is a developed water-soluble Curcuma longa extract containing 14% w/w curcuminoids, hydroxypropyl-β-cyclodextrin, and polyvinylpyrrolidone K30. This study aimed to investigate the biomolecular effects of CRE-Ter on differentiation of bone cells (murine MC3T3-E1 preosteoblasts), muscle cells (murine dexamethasone-treated C2C12 myotubes) atrophy and irisin expression. In MC3T3-E1 preosteoblasts, CRE-Ter treatment increased alkaline phosphatase activity, calcium deposition, and expression of Bmp-2, Runx2, and collagen 1a significantly and dose-dependently. 5, 10, and 20 µg/mL CRE-Ter upregulated β-catenin expression significantly. CRE-Ter improved the atrophy of dexamethasone-treated C2C12 myotubes. CRE-Ter decreased proinflammatory cytokine (TNF-α and IL-6) expression but increased FNDC5 and irisin expression and nitric oxide production in dexamethasone-treated C2C12 myotubes significantly and dose-dependently. Dexamethasone promoted β-catenin and total p38 expression in C2C12 myotubes. CRE-Ter at 2.5–20 µg/mL reversed the increase in β-catenin expression, whereas 2.5 µg/mL reversed total p38 expression. Crosstalk experiments further revealed that conditioned medium from C2C12 myotubes enhanced osteocalcin expression in MC3T3-E1 osteoblasts. Molecular docking simulations using CB-Dock2 showed strong interactions between each curcuminoid molecule and irisin. Therefore, CRE-Ter may stimulate osteoblast differentiation, ameliorate myotube atrophy, and increase irisin expression, indicating its therapeutic potential in osteoporosis, sarcopenia, and osteosarcopenia.